Early Feeding after Digestive Surgery: Is it Safe? - Christina, Edelyn (PT. Kalbe Farma Tbk., 2021)
Withholding nutrients following surgery until the resolution of intestinal function is not supported by scientific evidence. Early feeding after surgery consisted of a liquid diet within 24 hours after surgery, followed by the gradual increase of food consistency and amount until patients can tolerate solid feeding. However, the safety and efficacy of the procedure are still unclear.Praktik menghindari asupan nutrisi pasca-operasi hingga terdapat bukti resolusi fungsi pencernaan tidak didukung bukti ilmiah. Nutrisi dini berarti asupan nutrisi berupa diet cair dalam 24 jam pasca-operasi, diikuti peningkatan jumlah dan konsistensi makanan hingga pasien dapat menoleransi makanan padat. Masih terdapat kontroversi terkait keamanan dan efikasi prosedur nutrisi dini tersebut.Â